2004
DOI: 10.1161/01.cir.0000140676.88412.cf
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Angiogenesis

Abstract: Background-Ginseng is a commonly used nutraceutical. Intriguingly, existing literature reports both wound-healing and antitumor effects of ginseng extract through opposing activities on the vascular system. To elucidate this perplexity, we merged a chemical fingerprinting approach with a deconstructional study of the effects of pure molecules from ginseng extract on angiogenesis. Methods and Results-A mass spectrometric compositional analysis of American, Chinese and Korean, and Sanqi ginseng revealed distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
119
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 269 publications
(126 citation statements)
references
References 21 publications
(27 reference statements)
4
119
0
Order By: Relevance
“…It should be pointed out that Sengupta et al (2004), using similar concentrations of Rb1, showed an increase in FGF-2 þ TNFa and VEGF þ TNF-a-stimulated tubulogenesis in fibrin gels and matrix-driven network formation on the Matrigel. The reason for the discrepancy between the study appearing in this issue of British Journal of Pharmacology and the earlier report is unclear.…”
Section: Ginsenosides Altering Angiogenic Responsesmentioning
confidence: 91%
See 3 more Smart Citations
“…It should be pointed out that Sengupta et al (2004), using similar concentrations of Rb1, showed an increase in FGF-2 þ TNFa and VEGF þ TNF-a-stimulated tubulogenesis in fibrin gels and matrix-driven network formation on the Matrigel. The reason for the discrepancy between the study appearing in this issue of British Journal of Pharmacology and the earlier report is unclear.…”
Section: Ginsenosides Altering Angiogenic Responsesmentioning
confidence: 91%
“…Thus, there is great interest in the identification of the chemical entities that are responsible for the beneficial effects of such nutraceuticals. Panax ginseng presumably inhibits tumour growth by affecting both cancer cells and their blood supply (Yun, 2001;Sengupta et al, 2004). Using purified active ingredients from ginseng, researchers have identified so far three distinct ginseng saponins capable of affecting neovascularization and angiogenesis-related properties of ECs.…”
Section: Ginsenosides Altering Angiogenic Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the pharmacological actions of ginseng are attributed to a variety of ginsenosides, which are triterpenoid saponins (Attele et al, 1999;Huang et al, 2005). The physiological and medicinal effects of the various Science Publications AJAS ginsenosides differ and can even be oppositional (Sengupta et al, 2004;Joo et al, 2005). Since ginsenosides produce effects that differ from one another and a single ginsenoside initiates multiple actions, the overall pharmacology of ginseng is complex.…”
Section: Introductionmentioning
confidence: 99%